2013
DOI: 10.1111/j.1365-2761.2012.01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the protective efficacy of antigen combinations against Photobacterium damselae ssp. piscicida infections in cobia, Rachycentron canadum L.

Abstract: Cobia, Rachycentron canadum L., is a very important aquatic fish that faces the risk of infection with the bacterial pathogen Photobacterium damselae ssp. piscicida, and there are few protective approaches available that use multiple antigens. In the present study, potent bivalent antigens from P. damselae ssp. piscicida showed more efficient protection than did single antigens used in isolation. In preparations of three antigens that included recombinant heat shock protein 60 (rHSP60), recombinant α-enolase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 41 publications
0
2
0
2
Order By: Relevance
“…piscicida é um patógeno responsável pela doença denominada fotobacteriose (também conhecida como pasteurelose ou pseudotuberculose), de grande importância na aquicultura por ser encontrado globalmente em espécies de peixes marinhos cultivados (Romalde, 2002;Ho et al, 2014), como R. canadum (Liao et al, 2004), olhete (Seriola quinqueradiata) (Romalde, 2002), pargo europeu (Sparus aurata) (Andreoni & Magnani, 2014) e robalo europeu (Dicentrarchus labrax) (Korun & Timur, 2005).…”
Section: Photobacterium Damselae Subsp Piscicidaunclassified
See 1 more Smart Citation
“…piscicida é um patógeno responsável pela doença denominada fotobacteriose (também conhecida como pasteurelose ou pseudotuberculose), de grande importância na aquicultura por ser encontrado globalmente em espécies de peixes marinhos cultivados (Romalde, 2002;Ho et al, 2014), como R. canadum (Liao et al, 2004), olhete (Seriola quinqueradiata) (Romalde, 2002), pargo europeu (Sparus aurata) (Andreoni & Magnani, 2014) e robalo europeu (Dicentrarchus labrax) (Korun & Timur, 2005).…”
Section: Photobacterium Damselae Subsp Piscicidaunclassified
“…piscicida remontam ao final da década de 1980 e meados da década de 1990 (Romalde, 2014), e muito progresso ocorreu desde então, especialmente em virtude da uniformidade sorológica do patógeno, que facilitou o desenvolvimento de ferramentas de diagnóstico e também de vacinas específicas e eficientes (Thune et al, 2003;Romalde, 2014). Atualmente, existem vacinas específicas para P. damselae comercializadas por empresas internacionais (Gudding & Van Muiswinkel, 2013), além de pesquisas para o desenvolvimento de novas vacinas de segunda geração que prometem ser ainda mais eficientes (Ho et al, 2011(Ho et al, , 2014. Lin et al (2006) relataram produção de anticorpos uma semana após a injeção de P. damselae subsp.…”
Section: Fotobacteriose No Brasilunclassified
“…piscicida isolates [4]. Moreover, antigen combinations were studied revealing that bivalent subunit vaccines may achieve a better efficiency than monovalent or trivalent antigens [41]. …”
Section: Prevention Of P Damselae Subsp Piscicida Infectionmentioning
confidence: 99%
“…Several studies have reported the protection against P. damselae subsp. piscicida by different designs of vaccines in cultured fish [1][2][3][4][5]. Vaccines are usually composed of inactivated whole cells (bacterin), containing a wide pool of antigens.…”
mentioning
confidence: 99%